Planning Models and Their Implications for the Development of Islamic Educational Institutions - A Sibron; M.Sirozi (al-Afkar, Journal For Islamic Studies, 2025)
Educational planning is a crucial aspect of developing Islamic educational institutions. This article discusses holistic, adaptive, and flexible educational planning models and their implications for the development of Islamic educational institutions. This research employs a library research method by gathering data from relevant literature. The findings indicate that planning involving active stakeholder participation, integrating technology, and guided by visionary leadership can enhance educational quality, resource management efficiency, and institutional adaptability to global challenges. The article identifies several planning models, such as comprehensive, target setting, and PPBS models, which are relevant for application in Islamic educational institutions. These findings emphasize the importance of participatory and structured planning patterns in improving the overall quality of educational institutions.